Incidental capture and diversity of Elasmobranchii and Teleostei caught by red snapper and lobster fisheries in the Great Amazon Reef System - Marceniuk, Alexandre Pires; Soares, Bruno Eleres; Medeiros, Aline Paiva Morais; Caires, Rodrigo Antunes; Carvalho, Alfredo; Santos, Wagner Cesar Rosa Dos; Romão, João; Costa, Wesley Assunção Da; Muniz, Mairink Ribeiro; Abreu, Valdo Sena; Gadig, Otto Bismarck Fazzano [UNESP]; Rosa, Ricardo De Souza; et al. (Instituto Nacional de Pesquisas da Amazônia, 2025)
The Great Amazon Reef System is one of the least known mesophotic environments on the Atlantic coast of northern South America, threatened by oil and gas exploration projects and explored by different industrial fisheries. Here, we provide the first inventory of the cartilaginous and bony fishes captured by industrial fisheries of the red snapper and lobster in the Great Amazonian Reef System, including a list of species with ecological and conservation information, in addition to biogeographic considerations. A total of 143 species were recorded, with 17 elasmobranchs and 126 teleosts. A specimen likely representing a hybrid between Cephalopholis fulva and Cephalopholis furcifer (Serranidae) was also recorded. Community ecology descriptors were employed to explore the diversity patterns of the species captured by different fishing gears. Our results highlight the relevance of monitoring fishery activities to enhance knowledge of the biodiversity in poorly sampled areas and understanding the local impacts of human activities.

O Grande Sistema de Recifes da Amazônia é um dos ambientes mesofóticos menos conhecidos da costa do Atlântico no norte da América do Sul, ameaçado por projetos de exploração de petróleo e gás e explorado por diferentes pescarias industriais. Apresentamos aqui o primeiro inventário dos peixes ósseos e cartilaginosos capturados pela pesca industrial do pargo e da lagosta no Grande Sistema de Recifes da Amazônia, incluindo uma lista de espécies com informações ecológicas e de conservação, além de considerações biogeográficas. Um total de 143 espécies foram registradas, sendo 17 elasmobrânquios e 126 teleósteos. Um espécime representando um provável híbrido entre Cephalopholis fulva e Cephalopholis furcifer (Serranidae) também foi registrado. Descritores ecológicos de comunidades foram utilizados para explorar os padrões de diversidade das espécies capturadas por diferentes artes de pesca. Nossos resultados destacam a relevância do monitoramento das atividades pesqueiras para aumentar o conhecimento da biodiversidade em áreas pouco amostradas e a compreensão dos impactos locais de atividades humanas.
Captura acidental e diversidade de Elasmobranchii e Teleostei na pesca do pargo e lagosta no Grande Sistema de Recifes da Amazônia
Keywords: mesophotic corals; fisheries monitoring; fishing gears; Amazon River plume; corais mesofóticos; monitoramento pesqueiro; artes de pesca; pluma do Rio Amazonas